KOORNHOF, Pieter Gerhardus Jacobus Inventory of documents - KOORNHOF, Pieter Gerhardus Jacobus (ARCA, 2018)
Private papers of P.G.J. Koornhof, National Party MP Edenvale [1964-1966], Primrose [1966-1984], Minister of Immigration [1972-1976], Mines [1972-1976], Sport and Recreation [1972-1978], National Education [1976-1978], Plural Relations and Development [1978-1979], Co-operation and Development [1979-1984], Ambassador USA [1986-1991], Chairman of the President's Council [1984-1986].
COVERAGE In Process; 75,20 Metres. AUDIO CASSETTES IN ARCA COLLECTION = 16
Keywords: KOORNHOF, Pieter Gerhardus Jacobus; Inventories; Politicians; National Party